Subcapsular hematoma of the liver graft after liver transplantation: A case report - Suphapol, Jade; Sirichindakul, Boonchoo; Nivatvongs, Supanit; Komolmit, Piyawat; Poonyathawon, Sahadol (Chulalongkorn Medical Journal, 2023)
This report describes subcapsular hematoma of the liver graft after liver transplantation due to iatrogenic parenchymal injury. A 58-year-old woman underwent cadaveric liver transplantation for HCV cirrhosis with hepatocellular carcinoma. On the second postoperative day, the patient developed acute renal failure and hypovolemic shock. Ultrasonographic finding showed huge subcapsular hematoma in the right lobe of the liver. Relaparotomy finding revealed a huge subcapsular hematoma covering the entire anterior surface of the right lobe extended to the falciform ligament. Parenchymal injury due to liver compression by self-retaining retractor might be the cause of this subcapsular hematoma which is potentiated by associated coagulopathy from cirrhosis and massive blood transfusion. This experience suggests that the liver graft must be handled with special care to prevent potential mechanical injury.